Analysis of Company Organizational Support for Millennial Employee Loyalty through Organizational Culture Mediation - Maruba Sihombing; Iskandarini; Meilita Tryana Sembiring (GoAcademica Research & Publishing, 2023)
This study examines the effect that organizational support and organizational culture have on increasing the loyalty of millennial employees at PT. Mandiri Tunas Finance. This study uses a quantitative descriptive method. When collecting the required data, researchers will distribute questionnaires to research samples. Related to this, the population of this study are employees of PT. Mandiri Tunas Finance as of January 2022 aged <35 years, where based on calculations carried out using the formula in accordance with the guidelines for determining the sample in the Structural Equation Modeling study, there were 70 samples. After getting responses from 70 samples, the researcher will recapitulate the data from the respondents. After that, the researcher will analyze the research data using the Structural Equation model. The results of this research show that Organizational Support has an effect on Organizational Culture. Apart from that, Organizational Culture can also increase Millennial Employee Loyalty. Finally, Organizational Support has no effect on Millennial Employee Loyalty, while Organizational Culture can mediate the influence of Organizational Support on Millennial Employee Loyalty.